Tumor‐specific expression and detection of a CEST reporter gene. Issue 2 (27th April 2015) - Minn, Il; Bar‐Shir, Amnon; Yarlagadda, Keerthi; Bulte, Jeff W. M.; Fisher, Paul B.; Wang, Hao; Gilad, Assaf A.; Pomper, Martin G.
<x xml:space="preserve">Abstract</x> Purpose To develop an imaging tool that enables the detection of malignant tissue with enhanced specificity using the exquisite spatial resolution of MRI. Methods Two mammalian gene expression vectors were created for the expression of the lysine‐rich protein (LRP) under the control of the cytomegalovirus (CMV) promoter and the progression elevated gene‐3 promoter (PEG‐3 promoter) for constitutive and tumor‐specific expression of LRP, respectively. Using those vectors, stable cell lines of rat 9L glioma, 9LCMV‐LRP and 9LPEG‐LRP, were established and tested for CEST contrast in vitro and in vivo. Results 9LPEG‐LRP cells showed increased CEST contrast compared with 9L cells in vitro. Both 9LCMV‐LRP and 9LPEG‐LRP cells were capable of generating tumors in the brains of mice, with a similar growth rate to tumors derived from wild‐type 9L cells. An increase in CEST contrast was clearly visible in tumors derived from both 9LCMV‐LRP and 9LPEG‐LRP cells at 3.4 ppm. Conclusion The PEG‐3 promoter:LRP system can be used as a cancer‐specific, molecular‐genetic imaging reporter system in vivo. Because of the ubiquity of MR imaging in clinical practice, sensors of this class can be used to translate molecular‐genetic imaging rapidly. Magn Reson Med 74:544–549, 2015. © 2015 Wiley Periodicals, Inc.